The Auditory Cortex - Winer, Jeffery A.; Schreiner, Christoph E.; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
This volume is a summary and synthesis of the current state of auditory forebrain organization. It addresses a clinical and academic research area that has experienced substantial progress in understanding the contribution of the auditory forebrain (that is, the medial geniculate body, the auditory cortex, and limbic-related structures) to hearing, sound localization, communication, emotive behavior, and cognition. While much of this work has been summarized in brief review form, a more synoptic and integrative treatment has been needed. The Auditory Cortex looks back on 100 years of the discipline of auditory forebrain studies with a view to framing a future agenda. As new methods emerge and as older approaches exhaust their potential, it provides a summing up of the field and forges a prospectus for future work. The goal of this volume is to provide an experimental foundation and a conceptual framework for the auditory forebrain useful to the discipline as a whole, which one might consult as both a summary of work in progress and an invitation to explore further. The Auditory Cortex is a timely contribution in view of the growing interest in this network as the arbiter for hearing, and as a key element in the larger communications network that spans and links the parietal, temporal, and frontal cortices. It provides an introduction to the auditory forebrain and to the neural basis of central auditory processing for neuroscientists, psychologists, clinicians, otolaryngologists, and graduate and postgraduate research workers in the field of sensory and sensory-motor systems. About the Editors: Dr. Jeffery A. Winer was a Professor of Neurobiology in the Department of Molecular and Cell Biology at the University of California at Berkeley. He used structural studies of the central auditory pathway as a model system to address significant neurobiological questions about neural circuitry in a functional context. The comparative, structural, and functional accessibility of the central auditory pathway provided him with a powerful system in which to pursue functional questions in the context of systems neuroscience. Dr. Christoph E. Schreiner is Professor and Vice-Chair in the Department of Otolaryngology--Head and Neck Surgery and a Member of the W.M. Keck Foundation Center for Integrative Neuroscience and the Coleman Memorial Laboratory at the University of California at San Francisco. His main scientific interests are centered around the processing of complex sounds in the auditory midbrain, thalamus, and cortex.
Keywords: Life sciences; Neurosciences; Neurology; Otorhinolaryngology; Neurobiology; Life Sciences; Neurobiology; Neurosciences; Otorhinolaryngology; Neurology